Vitamin D receptor (VDR) gene polymorphism is associated with left ventricular (LV) mass and predicts left ventricular hypertrophy (LVH) progression in end‐stage renal disease (ESRD) patients - Testa, Alessandra; Mallamaci, Francesca; Benedetto, Francesco A; Pisano, Anna; Tripepi, Giovanni; Malatino, Lorenzo; Thadhani, Ravi; Zoccali, Carmine (Journal of bone and mineral research, 2010)
Left ventricular hypertrophy (LVH) is a strong cardiovascular risk marker in end‐stage renal disease (ESRD) patients. Vitamin D deficiency and/or disturbed vitamin D signaling has been implicated in LVH in experimental models. Because the BsmI vitamin D receptor VDR gene polymorphism may alter VDR function, we performed a cross‐sectional and longitudinal study in a cohort of 182 dialysis patients to investigate (1) the relationship between BsmI VDR gene polymorphism and left ventricular mass index (LVMI) measured by echocardiography and (2) the predictive power of this polymorphism for progression in LVH over a 18 ± 2 months of follow‐up. As a reference group, we used 175 healthy subjects matched to the study population as for age and sex. The distribution of BsmI genotypes did not significantly deviate from Hardy‐Weinberg equilibrium either in patients or in the control group of healthy subjects. The frequency of the B allele of BsmI polymorphism (40.4%) in dialysis patients was similar to that of healthy control subjects (38.6%), and the number of B alleles was directly related to LVMI (r = 0.20, P = .007). This relationship remained robust (β = 0.19, P = .006) in multivariate analysis adjusting for traditional and nontraditional risk factors and antihypertensive and calcitriol treatment. In the longitudinal study, LVMI rose from 60.1 ± 17.9 to 64.2 ± 19.3 g/m2.7 (P < .001), and again, the number of B alleles was associated with LVMI changes both in crude and in fully adjusted analyses. These cross‐sectional and longitudinal observations coherently support the hypothesis that altered vitamin D signaling is implicated in LVH in ESRD patients. © 2010 American Society for Bone and Mineral Research